PENGARUH KONSUMSI KAFEIN TERHADAP PREMENSTRUAL SYNDROME PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - WIDYA NINGSIH, PARAMITHA; CHALIL, MUHAMMAD JALALUDDIN ASSUYUTHI; AKBAR, AIDIL; WILDANI, HASBINA (LP2MTBM MAKARIOZ, 2023)
Premenstrual syndrome (PMS) is a condition in which a woman feels several changes in the body both physically, emotionally, and in behavior that occur before menstruation, so that it will interfere with daily activities and then disappear along with the end of the menstrual phase. The cause of this emergence is not clear. Some theories say, among others, due to hormonal factors, namely an imbalance between the hormones estrogen and progesterone. Experiencing other things, related to feeling disorders, psychological factors, social problems, or serotonin function experienced by sufferers. Behavioral factors are risk factors for premenstrual syndrome, one of which is caffeine consumption. The results of the study of the American College of Obstetricians and Gynecologists (ACOG) in Sri Lanka in 2012, reported that the symptoms of premenstrual syndrome experienced by around 65.7% of adolescent girls. The purpose of this study was to determine the effect of caffeine consumption on the incidence of premenstrual syndrome in students of the Faculty of Medicine, University of Muhammadiyah North Sumatra. This study is a descriptive-analytic study with a cross-sectional approach. The subjects of this study were students of the Faculty of Medicine, University of Muhammadiyah North Sumatra with a total of 87 people. This study uses a simple random sampling technique of data collection with chi-square test. Collecting data by filling out questionnaires. This study shows that there is a significant relationship between caffeine consumption and premenstrual syndrome as evidenced by a p-value of 0.017 (p<0.05). The conclusion there is an effect between caffeine consumption on the incidence of premenstrual syndrome